a ANALISIS PENDAPATAN KARYAWAN DEPO AIR MINUM ISI ULANG DI KECAMATAN TANJUNG REDEB: ANALISIS PENDAPATAN KARYAWAN DEPO AIR MINUM ISI ULANG DI KECAMATAN TANJUNG REDEB - Gilang Edwar (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2019)
ABSTRACT The purpose of this study which was conducted is to know the size of the income section have also been depot employees can be transferred to water water to drink in urban village tanjung redeb and compare it with the needs of decent living in kabupaten berau .Income section have also been depot employees can be transferred to drinking water drinking water in refilled bottle in kecamatan the cape of good redeb it should also be noted rata-rata as much as rp .4.392.000 per tens of thousands of workers in a month each of , with a value of up standard deviations as much as rp.793.950 .Based on analysis of the in the manner of a statistic by the use of a mark upon the fit and proper test level of confidence 95 % in a can the value of t has kept count of them as much as 14,368 while t table as much as 2,009 .Because the value of t has kept count of them is greater and mightier than t table , hence writers spurn and set at nought h0 and ha1 and he received and welcomed of alternative hypotheses 2 ( ha2 ) that the income tens of thousands of workers of sources of drinking water depot drinking water in refilled bottle in kecamatan the cape of good redeb start to diverge so painfully built with the sweat of the needs of decent living years 2017 is as much as rp .2,778.624 Keywords: income employees , for decent living ABSTRAK Tujuan Penelitian yang dilakukan adalah untuk mengetahui besarnya pendapatan karyawan Depo Air Minum di Kecamatan Tanjung Redeb dan membandingkannya dengan Kebutuhan Hidup Layak di Kabupaten Berau. Pendapatan karyawan depo air minum isi ulang di Kecamatan Tanjung Redeb secara rata-rata sebesar Rp. 4.392.000 per karyawan dalam satubulan, dengan nilai standar deviasi sebesar Rp.793.950. Berdasarkan analisis secara statistic dengan menggunakan uji t pada tingkat keyakinan 95% di dapat nilai t hitung sebesar 14,368 sedangkan t tabel sebesar 2,009. Karena nilai t hitung lebih besar dari t tabel, maka penulis menolak H0 dan Ha1 dan menerima hipotesis alternatif 2 (Ha2) bahwa pendapatan karyawan depo air minum isi ulang di Kecamatan Tanjung Redeb sudah berada diatas kebutuhan hidup layak Tahun 2017 yaitu sebesar Rp. 2,778.624. Kata Kunci :Pendapatan Karyawan, Kebutuhan Hidup Layak